EFEKTIVITAS KOORDINASI BAPPERIDA DALAM PENYELENGGARAAN KEBIJAKAN PAUD HOLISTIK INTEGRATIF - Margareta Febriyanti More Mangara Putri; Imanuel Wellem; Paulus Juru (Universitas Nusa Nipa Maumere, 2026)
This research analyzed the effectiveness of the Regional Planning, research, and Innovatiom Agency in implementing the Holistic Integrative Early Choldhood Education Policy in Sikka Regency. This research used a descriptive qualitative approach through interviews and documentation. The findings indicated that the regional development planning, research, innovation agencys coordination was relatively effective, as reflected in structured communication, clear division of tasks, and the participation of regional government agencies. However, strengthening cross-sectoral coordination was still needed, particularly at the village level.